Benefits of tailored hepatocellular carcinoma screening in patients with cirrhosis on cancer‐specific and overall mortality: A modeling approach. Issue 10 (25th August 2022) - Ningarhari, Massih; Mourad, Abbas; Delacôte, Claire; Ntandja Wandji, Line‐Carolle; Lassailly, Guillaume; Louvet, Alexandre; Dharancy, Sébastien; Mathurin, Philippe; Deuffic‐Burban, Sylvie
Abstract: To validate cancer screening programs, experts recommend estimating effects on case fatality rates (CFRs) and cancer‐specific mortality. This study evaluates hepatocellular carcinoma (HCC) screening in patients with cirrhosis for those outcomes using a modeling approach. We designed a Markov model to assess 10‐year HCC‐CFR, HCC‐related, and overall mortality per 100, 000 screened patients with compensated cirrhosis. The model evaluates different HCC surveillance intervals (none, annual [12 months], semiannual [6 months], or quarterly [3 months]) and imaging modalities (ultrasound [US] or magnetic resonance imaging [MRI]) in various annual incidences (0.2%, 0.4%, or 1.5%). Compared to no surveillance, 6‐month US reduced the 10‐year HCC‐CFR from 77% to 46%. With annual incidences of 0.2%, 0.4%, and 1.5%, the model predicted 281, 565, and 2059 fewer HCC‐related deaths, respectively, and 187, 374, and 1356 fewer total deaths per 100, 000 screened patients, respectively. Combining alpha‐fetoprotein screening to 6‐month US led to 32, 63, and 230 fewer HCC‐related deaths per 100, 000 screened patients for annual incidences of 0.2%, 0.4%, and 1.5%, respectively. Compared to 6‐month US, 3‐month US reduced cancer‐related mortality by 14%, predicting 61, 123, and 446 fewer HCC‐related deaths per 100, 000 screened patients with annual incidences of 0.2%, 0.4%, and 1.5%, respectively. Compared to 6‐month US, 6‐month MRI (−17%) and 12‐month MRI (−6%) reduced HCC‐related mortality. Compared to 6‐month US, overall mortality reductions ranged from −0.1% to −1.3% when using 3‐month US or MRI. A US surveillance interval of 6 months improves HCC‐related and overall mortality compared to no surveillance. A shorter US interval or using MRI could reduce HCC‐CFR and HCC‐related mortality, with a modest effect on overall mortality.